Highland teenagers: Their understanding and practice towards water ecology - Embong, A.M. (Medwell Journals, 2017)
Unlike most places in this modern world, most of the rural highlands are not accessible to the basic infrastructures like water, electricity or internet. For the inhabitants, natural sources like rain, good soil or forest are the god's gifts that need to be treated fairly. This study looks at the understanding and practice of the teenagers in the highland in one of the most remote areas in Malaysia towards the water ecology. A survey was carried out among the 102 teenagers who are still remaining in the highlands. The findings reveal that the teenagers have a good understanding and practice towards the water ecology. Even most of respondents are not aware the written law pertaining the aquatic life they treat the subject matter as something to be treasured and precious in their life. © Medwell Journals, 2017.